Insomnia is not a Risk Factor for Impaired Cognitive Function in Elderly - yudhiakuari sincihu; Nita Kurniawati (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2018)
Background: Elderly are often considered as a burden because of their physical limitations. Reduced cognitive function is one of the important causes for this physical limitation. Quality of sleep used to be associated with changes in cognitive function. Methods: A comparative analytic research to assess insomnia as a risk factor for the incidence of cognitive function impairment in the elderly. A case control study in elderly community at the nursing home St.Yosef, Surabaya. Result: Fifty respondents were taken by consecutive sampling and meeting the inclusion criteria. This study also excluded people with depression, schizophrenia, and users of psychotropic drugs. Eighty four percent of respondents with impaired cognitive function. Not much difference in percentage of insomnia disturbance in control group (37,5%) and case group (35,8%). Fisher's Exact Test show Sig.0,609 and OR=0.926 on CI [(0,194),(4,425)]. Conclusion: It was concluded that insomnia alone was not a risk factor for impaired cognitive modalities. Elderly exposed to sleep disorders have the same tendency to suffer cognitive impairment with unexposed.